(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Early mathematical concepts are formed for students in the pre-school age. As a result of the reforms in our country, the demand for qualified personnel and mature specialists in all fields is growing as economic growth is achieved. This in itself requires increasing the interest of students in the lessons and increasing the attention of teachers to comprehensive education. A number of changes in the field of education and the introduction of new innovative ideas in order to bring young people up in all respects and competently require great strength and deeply mastered knowledge and skills from all employees in the field of education. As a result, the staff of each industry works on their own, more than ever before, and strengthens their knowledge. In addition, the countries of Southeast Asia, Europe and the Americas, which have been taking place all over the world for 10-15 years, Every three years, the International Program for Assessing the Level of Education for Schoolchildren (PISA) examines the quality of the education system in the world. The PISA International Assessment Program aims to study the extent to which students aged 14-15 in different countries are mastering knowledge in mathematics, natural science, and reading, and using them in various areas of future activity.